Witch Hunting and Prosecuting in Early Modern Italy: A Historiographical Survey - Michaela Valente (Religions, 2023)
This article critically assesses Italian scholarship on the history of witchcraft over the last 60 years. Beginning with Carlo Ginzburg’s influential Night Battles (published in 1966 and translated to English in 1983) and ending with the recent work of Matteo Duni, Tamar Herzig, Vincenzo Lavenia and Louise Nyholm Kallestrup, the article traces the intellectual contexts and shifts in historiographical debates.